AYURVEDIC MANAGEMENT OF STARGARDTS MACULAR DEGENERATION- A CASE REPORT - Karunakaran, Sreekumar; S Nair, Arathi (International Journal of Ayurveda and Pharma Research, 2017)
Stargardts disease is a juvenile macular dystrophy which tends to appear between the ages of 10 to 20, although visual impairment may not be apparent until as late as ages 30 to 40.  Visual acuity including colour vision testing, visual field analysis, ERG, Fundus Fluorescein Angiography and Amsler grid charting are the useful diagnostic techniques for this disease. Even though significant research is taking place in this area, no treatment is available till date for this disease and general approach of macular degeneration is following now. In Ayurveda by considering the visual disturbance and field defect, this disease can be included under one the 12 types of Drishtigata rogas. Pitthavidagdhadrishti is one of the disease explained by Acharya Susrutha in Drishtirogas is more appropriate to define this clinical condition. As there is no common line of management following in these types of diseases in Ayurveda, an attempt has been made to explain a case treated as per the Ayurvedic principles. This article describes a30 year old male patient diagnosed as Stargardts macular degeneration and underwent Ayurvedic treatment protocol starting from the Snehapana and ending with Yogavasthi. By executing the Ayurvedic treatment, the quality of the vision mainly color perception including distant and near acuity is improved at least for a period of four years. The distant vision improved up to 6/24 and near vision N6 (P) in better eye.  The treatment methodology adopted in this case can be taken as a guideline to manage the macular degenerative diseases which need extensive management to tackle the pathology.